Apparent sympatry of Stiphrornis pyrrholaemus Schmidt & Angehr, 2008 and S. xanthogaster Sharpe, 1903 (Passeriformes: Muscicapidae) in Gabon, and taxonomic implications - Boano, Giovanni; Vinals, Nestor; Durante, Antonio; Pavia, Marco (Zootaxa, 2015)
We report the occurrence of the recently-described Stiphrornis pyrrholaemus in the Makokou area, northeastern Gabon, more than 600 kilometers NE from its type locality, in areas covered by dense primary to secondary forest. The previous records of Stiphrornis from the same area were referred to S. xanthogaster. We confirm this attribution on the basis of museum specimens. Although several recent sources treat all Stiphrornis as a single species, our findings strongly suggest the sympatric coexistence of two Stiphrornis species and thus that they should be treated as separate species under the Biological Species Concept.